2020
DOI: 10.1007/s40120-020-00189-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Analysis for Plasma β-Amyloid, Tau and Neurofilament Light (ATN) in World Trade Center Responders at Midlife

Abstract: Introduction: World Trade Center (WTC) responders who aided in the search and rescue efforts are now at midlife, and evidence has demonstrated that many are experiencing earlyonset cognitive impairment and are at risk of developing dementia, such as Alzheimer's disease (AD). According to the recent NIA-AA framework, AD is characterized by a neuropathological cascade commencing with bamyloid deposition (A), followed by tauopathy (T) and neurodegeneration (N). However, the ATN model has not been replicated utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Investigating neurodegenerative mechanisms, a recent pilot study ( n = 34) examined plasma-based neuropathological biomarkers in WTC responders and found an association between PTSD and reduced plasma amyloid-β (Aβ) and increased Aβ42/Aβ40 ratios suggesting a neurodegenerative pathway [ 150 ]. This was further supported by a follow-up study of a much larger sample of WTC responders at midlife ( n = 398), which showed that amyloid-1–42 and total tau distributions were associated with increased risk of cognitive impairment in this population [ 71 ]. Finally, recent work examining gene expression among responders with PTSD first identified ( n = 324) differential expression of two genes (NDUFA1, CCDC85B) previously found to be dysregulated in neurodegenerative disorders [ 158 ] and, when interrogating gene expression in cell subpopulations among responders ( n = 39) with/without PTSD, also identified PI4KAP1, REST, and SEPT4 genes in monocyte populations that have been previously implicated in neuronal loss and neurogenesis [ 159 ].…”
Section: Research Portfoliomentioning
confidence: 79%
See 1 more Smart Citation
“…Investigating neurodegenerative mechanisms, a recent pilot study ( n = 34) examined plasma-based neuropathological biomarkers in WTC responders and found an association between PTSD and reduced plasma amyloid-β (Aβ) and increased Aβ42/Aβ40 ratios suggesting a neurodegenerative pathway [ 150 ]. This was further supported by a follow-up study of a much larger sample of WTC responders at midlife ( n = 398), which showed that amyloid-1–42 and total tau distributions were associated with increased risk of cognitive impairment in this population [ 71 ]. Finally, recent work examining gene expression among responders with PTSD first identified ( n = 324) differential expression of two genes (NDUFA1, CCDC85B) previously found to be dysregulated in neurodegenerative disorders [ 158 ] and, when interrogating gene expression in cell subpopulations among responders ( n = 39) with/without PTSD, also identified PI4KAP1, REST, and SEPT4 genes in monocyte populations that have been previously implicated in neuronal loss and neurogenesis [ 159 ].…”
Section: Research Portfoliomentioning
confidence: 79%
“…Consequentially, cancer research accounts for a large portion (21%) of the funds awarded. There are descriptive and analytic studies examining cancer mortality and incidence, with a few studies examining mechanisms or treatment [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. There are also notable reviews [ 77 , 78 ].…”
Section: Research Portfoliomentioning
confidence: 99%
“…A cohort study of 398 WTC responders applied the AT(N) model [ 26 ] using plasma-based markers for Aβ 42 and Aβ 40 for Aβ (A), total tau for tauopathy (T), and NfL for neurodegeneration (N) [ 101 ]. This study built upon a pilot study of 34 WTC responders without concomitant head injury that showed an association between increased PTSD and decreased plasma Aβ load and increased Ab42/Ab40 ratios [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study built upon a pilot study of 34 WTC responders without concomitant head injury that showed an association between increased PTSD and decreased plasma Aβ load and increased Ab42/Ab40 ratios [ 4 ]. Results from the larger study [ 101 ] showed that WTC responders with cognitive impairment had higher age, lower raw mean plasma levels of Aβ 42 and a higher ratio of Aβ 40 :Aβ 42 . These findings support the AT(N) pathways and showed that Aβ 40 plays an intermediary role linking the proliferation of tau with changes in neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for this effect that has been offered is that microglia, which are activated in cerebrovascular disease [39], are also central to more rapid proliferation of protein-tau [40]. Additionally, researchers have posited that the amyloid cascade may require both the deposition of β-amyloid 1–42 throughout the cerebrum and the inclusion of β-amyloid 1–40 in the vasculature in order to cause neurodegeneration [41]. In either case, these results support a growing body of research suggesting that AD is worsened by the presence of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%